(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The need for medical rehabilitation of children with disabilities remains extremely high and accounts for at least 95% of their total number. Cerebral palsy (CP) constitutes approximately 24% of all neurological diseases. Childhood disability resulting from this pathology represents one of the most urgent medical and social problems of modern society and has national significance. In this context, it is essential to improve the quality of medical care, enhance early diagnosis of disabling diseases, develop and refine modern high-technology treatment methods, and implement effective preventive strategies. Transcranial magnetic stimulation (TMS) is a non-invasive method of brain stimulation that evaluates corticospinal tract conductivity through modulation of cortical excitability and depolarization of corticospinal neurons. As a non-invasive and painless technique, TMS applies electromagnetic principles to specific brain regions, regulating the functional activity of different cortical areas by altering neuronal excitability. Currently, TMS is increasingly used in the treatment of children with cerebral palsy. It has been shown to improve motor function, reduce spasticity, restore speech function, and modulate brain function through enhancement of neuroplasticity in patients with CP.